Kajian benefit tenaga kerja dalam kinerja melaksanakan tugas pada PT. Kelola Mina Laut PPS Kota Kendari - Amaliyah, Salsabila Khulaydah; La Ola, La Onu; Rosmawati; Nurdiana A; Sriwulan, Desy (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims (1) to determine the performance and system of providing benefits (bonuses) to labor, (2) to determine the provision of benefits can improve labor performance. The research was conducted in July 2023 at PT Kelola Mina Laut PPS Kendari City. This research uses a qualitative approach. Respondents in this study were daily workers totaling 10 people and piece workers totaling 12 people at PT. Kelola Mina Laut PPS Kendari City. The data analysis technique uses qualitative data sourced from Miles and Huberman. Consists of data collection, data reduction, data presentation, and conclusion drawing or verification. Based on the results of the research conducted, it can be concluded that (1) the performance and system of providing benefits (bonuses) to workers in the field of processing ball-ball octopus and frozen flowers who get benefits, namely workers who are able to work beyond the performance target of 1 kg, the benefits obtained are Rp.3,000 / kg, where daily workers are given benefits based on the number of tasks completed per person, while piece workers are given benefits based on the results of joint task work which then the total benefits obtained will be divided equally to the piece workers who participate in the work, (2) by providing benefits to the workforce of PT Kelola Mina Laut, the workers feel motivated to work harder and harder so as to improve their own performance at work in achieving work targets and company targets.